2007
DOI: 10.1086/520531
|View full text |Cite
|
Sign up to set email alerts
|

Gas Feedback on Stellar Bar Evolution

Abstract: We analyze evolution of live disk-halo systems in the presence of various gas fractions, f_gas less than 8% in the disk. We addressed the issue of angular momentum (J) transfer from the gas to the bar and its effect on the bar evolution. We find that the weakening of the bar, reported in the literature, is not related to the J-exchange with the gas, but is caused by the vertical buckling instability in the gas-poor disks and by a steep heating of a stellar velocity dispersion by the central mass concentration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
197
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(213 citation statements)
references
References 49 publications
14
197
2
Order By: Relevance
“…Contrary to what was found by Berentzen et al (2007), the introduction of gas does not damp the buckling instability, in the models considered here (both in MOND and DM). In MOND, without gas, the mass concentration in the Sc-model is lower in the centre, and the position of the vertical instability occurs at a larger radius, leading to a less conspicuous box-peanut shape in the edge-on view.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what was found by Berentzen et al (2007), the introduction of gas does not damp the buckling instability, in the models considered here (both in MOND and DM). In MOND, without gas, the mass concentration in the Sc-model is lower in the centre, and the position of the vertical instability occurs at a larger radius, leading to a less conspicuous box-peanut shape in the edge-on view.…”
Section: Discussioncontrasting
confidence: 99%
“…On the average, it appears 2−3 Gyr after the beginning of the simulation in the DM model against 4−5 Gyr in the MOND model. Bars are weakened during the buckling (Berentzen et al 2007), but this is not the only way. The MOND-Sc simulation with gas does not have a strong peanut, but the bar is weakened because the instability is too violent during a short period: the bar strength increases to 0.4 in less than 1 Gyr.…”
Section: Vertical Structurementioning
confidence: 99%
“…For example, Cheung et al (2015) found "no significant differences in the stellar populations of the bulges or the gradients of barred versus unbarred quiescent disk galaxies". However, modern simulations at least indicate that bars, once formed, are difficult to dissolve (in the absence of major mergers), unless the disc is extremely gas-rich Bournaud et al 2005;Berentzen et al 2007;Kraljic et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the bar could have grown in size and slowed trhough disk evolution (Sellwood 1981;Berentzen et al 2007) or halo friction (Athanassoula 2002, see §9.8), or have been triggered by large density fluctuations in the disk (Sellwood 1989a), by tidal interactions (Noguchi 1987;Berentzen et al 2004;Curir et al 2006), halo substructure (Romano-Díaz et al 2008b) or a non-axisymmetric halo (Dubinski & Chakrabarty 2009). Any of these considerations, or that described in the next paragraph, could plausibly reconcile the existence of bars in these galaxies with Toomre's stabilizing mechanism.…”
Section: Origin Of Barsmentioning
confidence: 99%